Strategi Komunikasi Pemasaran Kopi Kenangan (Studi Konten YouTube tentang Perkembangan Bisnis Kopi Kenangan) - Indah, Meutia; Saputra, Datep Purwa; Ayuna, Novianty Elizabeth (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This research aims to analyze Kopi Kenangan's marketing communication strategies through YouTube content, as well as to identify obstacles in consistently achieving the Top of Mind position in Indonesia's coffee shop market until 2025, considering fluctuations in its Top Brand Award index. This study employs a qualitative approach with a case study on Kopi Kenangan. Data were collected through triangulation: (1) an in-depth content analysis of three "Endgame" podcast series featuring Edward Tirtanata on YouTube (September 2020), (2) in-depth interviews with nine informants (three store managers, three store employees from ARION, MOI, and SPBU outlets, and three customers), and (3) documentation study on Kopi Kenangan's business development. Data analysis was conducted using the frameworks of Marketing Communication Theory and Push-Pull-Pass Marketing Communication Strategy Theory. The research findings identify Kopi Kenangan's marketing communication pattern as an integrated hybrid model. This model effectively combines digital push strategies through application notifications and social media promotions (implicitly including YouTube), with pull strategies focused on brand storytelling, in-store experiential marketing, and product education. Additionally, there is strong personal communication (pass strategy) from store staff, as well as extensive collaboration with delivery platforms to expand reach. Edward Tirtanata's disruptive vision also serves as the foundation for the strategically conveyed brand narrative. Although this pattern is effective in building awareness and driving purchases, consistent Top of Mind status is still hindered by internal inconsistencies in message delivery by employees, challenges in micro-level communication adaptation based on location, and the need to strengthen a unique and consistent brand narrative through storytelling content on YouTube to create cognitive dominance in consumers' minds.